The Interplay of EFL Students’ Enjoyment, Hope, Pride and Self-Regulation - Yin, Xuehong (Frontiers in Psychology, 2021)
Nowadays, emotions are among the most significant issues in the route of learning a language that should be taken into consideration. Consistent with the fundamental function of positive psychology (PP) and also the theory of broaden-and-build, enjoyment in language learning especially the foreign language is among those positive emotions that encourage EFL learners to develop their perspective to achieve. Efforts to apprehend and develop the academic achievement of EFL learners have also progressively concentrated on self-regulation as it boosts learners’ enjoyment, hope, pride, self-control, and learning. Besides, in line with the investigations of these positive emotions, principles of PP, the present review makes every effort for the interplay and its effects in language learning. It is pertinent to state that the present review of studies can benefit academic organizations, professional development centers, policymakers in the academic community to consider the role of emotions, namely positive ones and their positive impact on language learning.